2023
DOI: 10.1002/fsn3.3714
|View full text |Cite
|
Sign up to set email alerts
|

Use of different food additives to control browning in fresh‐cut potatoes

Guoqin Li,
Xinxin Wang,
Hongmei Zhu
et al.

Abstract: Fresh‐cut potato browning is a severe problem in the potato processing industry. Ascorbic acid, L‐cysteine, hydrogen sulfide (H2S), and nitric oxide (NO) have been reported to reduce the browning in fresh‐cut vegetables and fruits. We compared the effect of each food additive at its commonly used concentration on fresh‐cut potato browning in order to choose a highly efficient treatment and explore its mechanism. Fresh‐cut potato slices were immersed in 0.3 mmol L−1 ascorbic acid, 0.7 mmol L−1 L‐cysteine, 0.7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Although it has been widely studied the use of cysteine as an anti-browning agent [18,23,24,29], in the present study, it has been observed that non-treated and cysteinetreated artichokes presented similar WL; therefore, the use of cysteine on its own did not reduce the WL of fresh-cut artichoke, while its combination with EOs did. Similar results were observed in fresh-cut potatoes treated with L-cysteine, where no effect on WL was observed [55]. However, previous studies showed that the application of EOs resulted in a reduction of WL in litchi fruit [56], apricots [57], nectarines [58], grapes [59] and pears [60].…”
Section: Effect Of the Application Of Cysteine And Eos On Quality Par...supporting
confidence: 82%
“…Although it has been widely studied the use of cysteine as an anti-browning agent [18,23,24,29], in the present study, it has been observed that non-treated and cysteinetreated artichokes presented similar WL; therefore, the use of cysteine on its own did not reduce the WL of fresh-cut artichoke, while its combination with EOs did. Similar results were observed in fresh-cut potatoes treated with L-cysteine, where no effect on WL was observed [55]. However, previous studies showed that the application of EOs resulted in a reduction of WL in litchi fruit [56], apricots [57], nectarines [58], grapes [59] and pears [60].…”
Section: Effect Of the Application Of Cysteine And Eos On Quality Par...supporting
confidence: 82%